1999
DOI: 10.1677/jme.0.0220125
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cyclo-oxygenase types-1 and -2 in human fetal membranes throughout pregnancy

Abstract: Human labour is associated with increased prostaglandin synthesis within the fetal membranes. We have studied the expression of the two isoforms of the central prostaglandin synthetic enzyme, cyclooxygenase (COX-1 and COX-2), in human fetal membranes throughout pregnancy, at mRNA, protein and activity levels.COX-1 mRNA expression was low in human amnion and chorion-decidua and did not change with gestational age. COX-2 mRNA expression in fetal membranes increased with gestational age, with significant up-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(66 citation statements)
references
References 25 publications
(33 reference statements)
4
61
1
Order By: Relevance
“…However, antibodies against the currently recognised prostanoid receptors are not available and radio-ligand binding is limited due to the lack of truly specific ligands (Coleman et al 1990). However, previous studies of key systems involved in parturition have initially focused on mRNA and highlighted physiologically important regulators of the process, such as nitric oxide (Ali et al 1997) and cyclo-oxygenase-2 (COX-2) (Slater et al 1999). While our studies on prostanoid receptors in these tissues are, therefore, preliminary, we hypothesize that the observed changes in mRNA may reflect an important role for a direct effect of PGs on the control of the choriodecidua in labour.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, antibodies against the currently recognised prostanoid receptors are not available and radio-ligand binding is limited due to the lack of truly specific ligands (Coleman et al 1990). However, previous studies of key systems involved in parturition have initially focused on mRNA and highlighted physiologically important regulators of the process, such as nitric oxide (Ali et al 1997) and cyclo-oxygenase-2 (COX-2) (Slater et al 1999). While our studies on prostanoid receptors in these tissues are, therefore, preliminary, we hypothesize that the observed changes in mRNA may reflect an important role for a direct effect of PGs on the control of the choriodecidua in labour.…”
Section: Discussionmentioning
confidence: 79%
“…Characteristically, genes encoding signal transduction proteins which have a role in labour are expressed at higher levels in tissues (both myometrial and non-myometrial) from animals which are in labour, and there are many examples of such phenomena (Tabb & Garfield 1992, Wu et al 1996, Ou et al 1997, Slater et al 1999. As an initial test of our hypothesis that PG receptors have a direct role in the control of the chorion and decidua around labour, we sought to determine whether expression of these genes varied according to gestational age and whether the animal was in labour or not in labour at the time the tissue was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Here, COX-2 may be involved in the implantation of the ovum, in the angiogenesis needed for the establishment of the placenta, and in the induction of labor (Gibb and Sun, 1996). It has recently become clear that up-regulation of COX-2 expression mediates increased prostaglandin synthesis in the human myometrium (Slater et al, 1999a) and within the fetal membrane (Slater et al, 1999b) at term. In a subsequent study (Sawdy et al, 2000), specific COX-2 inhibitors were shown to be as effective as nonselective NSAIDs in inhibiting fetal membrane prostaglandin synthesis, suggesting that these drugs may also represent a new strategy for the treatment of tocolysis.…”
Section: Cox-2 and Reproductive Functionsmentioning
confidence: 99%
“…However, the factors responsible for changes in PGE 2 levels in the perinate have not been clearly identified. COX-2 is developmentally regulated (18,43,45,46), but this cannot explain the relatively selective increase in PGE 2 during the perinatal period (1,24). On the other hand, specific ontogenic changes in PGES isoforms may be responsible for this developmental process; if so, selective regulation of PGE 2 synthesis may constitute a novel approach for controlling DA tone.…”
mentioning
confidence: 99%